Why Music Therapists Choose to Work with a Clinical Population: An International Pilot Survey - Gilboa, Avi; Wiess, Chava; Dassa, Ayelet; Brotons, Melissa-Mercadal; Frank-Bleckwedel, Eva; Kaczynski, Elisabeth; Kantor, Jiri; Roelcke, Beate; Sabbatella, Patricia (International journal of environmental research and public health, 2022)
(1) Background: Throughout their career, music therapists make decisions regarding the clinical population they choose to work with. Though such decisions can have broad implications on the professional development of the music therapist, not much is known about the reasons for making these decisions and whether they are affected by demographic or professional factors. (2) Methods: In this pilot study, we surveyed 439 music therapists from six countries (i.e., Austria, the Czech Republic, Germany, Israel, Spain, and Switzerland) using an online questionnaire. We asked the respondents to explain why they chose to work with their main clienteles, and we examined whether their reasons were connected to demographic factors such as country of origin, gender, and seniority, and professional factors such as experience as a music therapist and population one works with. (3) Results: The category analysis of these responses pointed at nine distinct reasons that could be grouped into "practical reasons", "reasons of connection", and "innovation". There were differences in reasoning between music therapists from different countries, and with different degrees of seniority, but not between male and female music therapists. (4) Discussion: The implications on training programs and on policy makers are discussed as well as the importance of this subject to the development of music therapists' professional identity.
Keywords: ženské pohlaví; Music Therapy; lidé; průzkumy a dotazníky; pomocný zdravotnický personál; mužské pohlaví; Female; Male; Pilot Projects; muzikoterapie; Music; Surveys and Questionnaires; pilotní projekty; Allied Health Personnel; hudba; Humans